2004
DOI: 10.1038/ni1128
|View full text |Cite
|
Sign up to set email alerts
|

Conditional deletion of Gata3 shows its essential function in TH1-TH2 responses

Abstract: Expression of the transcription factor GATA-3 is strongly associated with T helper type 2 (T(H)2) differentiation, but genetic evidence for its involvement in this process has been lacking. Here, we generated a conditional GATA-3-deficient mouse line. In vitro deletion of Gata3 diminished both interleukin 4 (IL-4)-dependent and IL-4-independent T(H)2 cell differentiation; without GATA-3, T(H)1 differentiation occurred in the absence of IL-12 and interferon-gamma. Gata3 deletion limited the growth of T(H)2 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
564
3
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 564 publications
(599 citation statements)
references
References 48 publications
29
564
3
3
Order By: Relevance
“…However, IL-4 was blocked, as demonstrated by inhibition of both IL-4 mRNA and serum IgE elevations, when B7 costimulation was abrogated. These studies thus demonstrate differential regulation of IL-4 and IL-13 in T cells by costimulatory molecules during the in vivo immune response, consistent with previous studies indicating that these Th2 cytokines can be differentially regulated by certain transcription factors [10,11]. Our studies further indicate that DX5 + cells are also a major source of IL-13.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, IL-4 was blocked, as demonstrated by inhibition of both IL-4 mRNA and serum IgE elevations, when B7 costimulation was abrogated. These studies thus demonstrate differential regulation of IL-4 and IL-13 in T cells by costimulatory molecules during the in vivo immune response, consistent with previous studies indicating that these Th2 cytokines can be differentially regulated by certain transcription factors [10,11]. Our studies further indicate that DX5 + cells are also a major source of IL-13.…”
Section: Discussionsupporting
confidence: 91%
“…However, other studies suggest that under certain circumstances IL-4 and IL-13 are regulated independently, and certain signaling pathways involving c-maf [10] and GATA-3 [11] can differentially regulate these two cytokines. Consistent with these findings, several in vivo studies have recently identified IL-4-independent elevations of IL-13 associated with an IFN-c-dominant response [8,12], although the cell surface or secreted molecules that induce the development of IL-13-expressing cells in this context remain uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Silencing of CD4 resulted in the expected impairment of antigen-dependent T-cell activation [13][14][15]. siRNA-mediated knockdown of the Th2 transcription factor GATA-3 abolished the expression of its target genes, the prototypic Th2 cytokines IL-4 and IL-5, as reported for GATA-3 knockout mice [17,18]. Noteworthy, the use of stabilized siRNA proved to be absolutely mandatory since conventional siRNA identical in sequence and tested for efficiency in cell lines turned out to be largely ineffective in these assays.…”
Section: Discussionmentioning
confidence: 93%
“…We chose GATA-3 as a target given that this transcription factor is critical for the development of Th2 cells from naïve T cells, which occurs in the first days after stimulation [16][17][18]. T cells were transfected with stabilized or conventional GATA-3 siRNA, a control siRNA (siGFP) or were nucleofected without siRNA.…”
Section: Sirna-transfected T Cells Remain Functional and Maintain Knomentioning
confidence: 99%
“…Second, using conditional Gata3 knockout mice, it was observed that deletion in CD4/CD8 double-negative thymocytes blocked T cell development at the DN3 stage [42]. Third, deleting npg cells, although development of CD8 single positive T cells appears normal [42,43]. We prepared a conditional Gata3 knockout by flanking exon 4 of the Gata3 gene with two loxP sites [43].…”
Section: The Central Role Of Gata-3 In Reinforcing Th2 Responsesmentioning
confidence: 99%